Why do users continue to contribute to darknet Child Sexual Abuse Material forums? Examining social exchange, social capital, and social learning explanations using digital forensic artifacts - Blokland, Arjan; Daser, Anton; de Boer, Meike; Gannon, Colm; Gnielka, Frederic; Huikuri, Salla; Reichel, Rebecca; Shäfer, Thomas; Schmidt, Alexander F.; Staciwa, Katarzyna; Lehmann, Robert (Child abuse & neglect, 2024)
The darknet hosts an increasing number of hidden services dedicated to the distribution of child sexual abuse material (CSAM). Given that by contributing CSAM to the forum members subject themselves to criminal prosecution, questions regarding the motivation for members contributing to darknet CSAM forums arise. Building on insights gained from research into clearnet communities, here we examine the extent to which social incentives generated by the online CSAM community may explain members' posting behavior on darknet CSAM forums. We analyze digital forensic artifacts on the online behavior of members of a darknet CSAM forum that was shut down by law enforcement agencies in July 2015. We apply group-based trajectory modelling (GBTM), social network analysis, and mixed-effect survival models. Applying GBTM three posting trajectories can be distinguished. Social network analyses finds the reply network to be more centralized than predicted by chance. Mixed-effect survival models show positive associations between the length of members' first post and the time since members' first registration on the forum and subsequent posting. Contrarily, the number of replies received appears to mitigate subsequent posting. Findings show posting activity on the forum to be concentrated in a minority of forum members who show posting trajectories that are both frequent and persistent. Results further suggest persistence in posting is motivated by social identity and, to a lesser extent, differential association processes. •Only a minority of darknet CSAM forum members participates in public forum communications.•Even among active forum members, a minority of members generates the bulk of public communications.•Forum members’ continued contributing is associated with self-presentation and prolonged exposure to the forum environment.•Unexpectedly, peer feedback seems to mitigate continued participation.